Herpes Simplex Virus 1 Blocks Caspase-3-Independent and Caspase-Dependent Pathways to Cell Death - Galvan, Veronica (American Society for Microbiology, 1999)
Earlier reports have shown that herpes simplex virus 1 (HSV-1) mutants induce programmed cell death and that wild-type HSV blocks the execution of the cell death program triggered by viral gene products, by the effectors of the immune system such as the Fas and tumor necrosis factor pathways, or by nonspecific stress agents such as either osmotic shock induced by sorbitol or thermal shock. A report from this laboratory showed that caspase inhibitors do not block DNA fragmentation induced by infection with the HSV-1 d120 mutant. To identify the events in programmed cell death induced and blocked by HSV-1, we examined cells infected with wild-type virus or the d120 mutant or cells infected and exposed to sorbitol. We report that: (i) the HSV-1 d120 mutant induced apoptosis by a caspase-3-independent pathway inasmuch as caspase 3 was not activated and DNA fragmentation was not blocked by caspase inhibitors even though the virus caused cytochrome c release and depolarization of the inner mitochondrial membrane. (ii) Cells infected with wild-type HSV-1 exhibited none of the manifestations associated with programmed cell death assayed in these studies. (iii) Uninfected cells exposed to osmotic shock succumbed to caspase-dependent apoptosis inasmuch as cytochrome c was released, the inner mitochondrial potential was lost, caspase-3 was activated, and chromosomal DNA was fragmented. (iv) Although caspase-3 was activated in cells infected with wild-type HSV-1 and exposed to sorbitol, cytochrome c outflow, depolarization of the inner mitochondrial membrane, and DNA fragmentation were blocked. We conclude that although d120 induces apoptosis by a caspase-3-independent pathway, the wild-type virus blocks apoptosis induced by this pathway and also blocks the caspase-dependent pathway induced by osmotic shock. The block in the caspase-dependent pathway may occur downstream of caspase-3 activation.